Structural evolution during mechanical alloying and annealing of a Nb-25at%Al alloy - KIM, HYE SUNG; Kum, Dong wha; Hanada, S (Kluwer Academic Publishers, 2000)
Mixtures of pure elemental Al and Nb powders of Nb-25at%Al composition was mechanically alloyed, and structural evolution during high energy ball milling has been examined. Al dissolved in Nb from the early stage of the ball milling, and amorphization became noticeable after longer than five hours of milling. However the dissolution of Al in Nb was not completed before the amorphization. No intermetallic phase formed during the mechanical alloying. Before complete amorphization, metastable nitride of Nb4.62N2.14 (i.e., beta-NbN) with hexagonal structure has formed in nanocrystalline size through nitrogen incorporation from ambient environment. The lattice parameter of Nb increased significantly (up to 3.3433 Angstrom after 5 hours of milling) during the milling. Upon annealing above 950 degrees C, Nb2Al became the dominant feature with the beta-NbN, and Nb3Al did not form from the samples milled at ambient environment. Nb3Al appeared only from a sample milled at Ar environment. Structural evolution during mechanical alloying of the Nb-Al system is critically dependent the upon milling environment. (C) 2000 Kluwer Academic Publishers.